Зарубіжний досвід переходу до інноваційного типу розвитку аграрного сектору національної економіки - Павлова, Галина Євгеніївна; Pavlova, Halyna (Дніпровський державний аграрно-економічний університет, ТОВ `ДКС Центр`, 2011)
Розвиток аграрного сектору національної економіки України неможливо без інновацій, особливо в сільськогосподарському виробництві. Зараз перед аграрним сектором національної економіки України стоїть виключно складне завдання переходу від технологічної деградації до постіндустріального способу виробництва. Необхідність переходу економіки України на інноваційний шлях розвитку - це визнана точка зору серед інтелектуальної та владної еліти. Широко поширене уявлення, ніби інноваційний розвиток передбачає всього лише більш інтенсивне, ніж раніше, впровадження сучасних технологій у виробництво і в його організаційні структури. Зрозуміло, така позиція має право на існування. Разом з тим, анітрохи не применшуючи значення впровадження в практику новітніх наукових пошуків, технологій і методів організації виробництва, не можна не звернути уваги на серйозні вади такої свідомо звуженою трактування проблеми. Інноваційний шлях розвитку агропромислового виробництва має три взаємопов'язаних і взаємообумовлених напрямки нововведень: стосуються людського, біологічного, а також техногенного чинників. Особлива роль нововведень щодо біологічного фактора агровиробництва - відмінна риса інноваційних процесів у сільському господарстві, його техніко-технологічного оновлення в порівнянні з іншими секторами економіки. Для України розвиток аграрного сектору національної економіки - об'єктивна необхідність теперішнього часу, обумовлена не тільки економічними міркуваннями, а й історико-культурними умовами розвитку нашої країни. Наша країна може розвиватися і процвітати тільки за умови, що в нашій країні розвиватиметься сільське господарство. Україна - історично аграрна країна і, на відміну від інших країн, не може не розвивати сільське господарство. Development of the agricultural sector of the national economy of Ukraine is impossible without innovation, particularly in agriculture. Now the agricultural sector of the national economy Ukraine is extremely complex problem of transition from technological degradation to post-industrial mode of production. The need for economic transition in Ukraine innovative way of development - is recognized among the intellectual point of view and the ruling elite. The widespread idea that innovative development involves just more intense than before the introduction of modern technologies in production and its organizational structure. Of course, this position has the right to exist. However, no prejudice to the practical implementation of the latest scientific research, technology and methods of production, can not pay attention to such serious flaws deliberately narrowed interpretation problems. Reducing the idea of innovation to the obvious and absolute need regular updating of capital to greater use in the production process of scientific innovations and new technologies, we are depriving its inherent innovative content. Themselves innovation as a key element of social production has always been a primary element of human community. However, if innovation in the industry has always focused on one or a few very specific businesses with staff of designers and engineers, agricultural innovation is applicable in hundreds and thousands of farms with different volumes of production, technical and technological equipment and most importantly - with varying willingness to learn them people who make decisions and implement innovation. Innovators can make a lot just learning features innovations. They maintain links with science or, as now, becoming abroad: from seed to harvest technology. The middle is not always able to repeat this experience because it does not have the right conditions and knowledge. If there is no next innovators, they only learn about innovations in the long run. An innovative way of development of agricultural production has three interrelated and interdependent areas of innovation: related to human, biological and anthropogenic factors. The special role of biological factors on innovation in agricultural production - feature innovative processes in agriculture, its technical and technological renovation compared to other sectors. For Ukraine, development of the agricultural sector of the national economy - an objective necessity now, due not only to economic considerations, but also historical and cultural conditions of our country. Our country can develop and flourish only if in our country develop agriculture. Ukraine - historically an agricultural country and, unlike other countries, can not develop agriculture.
Foreign experience of transition to innovative type of development of the agricultural sector of the national economy
Keywords: інноваційна економіка; іnnovative еconomy; інновації; innovation; аграрний сектор; agriculture; національна економіка; national economy; соціально-економічні перетворення; socio-economic transformation